Implementasi Program Asistensi Rehabilitasi Sosial Bagi Keluarga Miskin Melalui Warung Makan Indomie Di Kota Bandung - Ajmala Sobri, Fahdina; Yaneri, Ahmad; Kartika, Tuti (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
This study examines the Social Rehabilitation Assistance Program (Atensi), which provides benefits for developing skills and knowledge to increase self-reliance. The focus of this research is the implementation of the Atensi program for poor families through Warung Makan Indomie (Warmindo) in Bandung City. Data were collected through observation, in-depth interviews, and documentation studies. The results showed that the distribution of assistance through the Warmindo program went quite smoothly, although there were some policy changes due to directives from the central ministry. The Beneficiary Families (KPM) experienced various changes in their conditions, including economic, social, physical, and psychological aspects. These changes were not always positive; sometimes, there were significant negative changes. This research highlights the distribution process of the assistance and the changes in the lives of the KPM from various aspects. Based on these issues, the researchers recommend the need for capacity building to develop the knowledge and skills of the KPM.